ABC-VED Analysis of a Drug Store in Rural Health Training Centre in Kanchipuram District in Tamilnadu - Mercy M; Newtonraj A; Lourdu Jafrin Antony; Rajini S; Anil J Purty (International Journal of Pharma and Bio Sciences, 2021)
ABC-VED matrix model is one of the effective inventory management techniques for the drugs used in a pharmacy. This technique was used for dividing the total inventory drugs into three categories in the Rural Health Training Centre at Chunampet located at Kanchipuram district of Tamilnadu, attached to the Department of Community Medicine, PIMS. The Annual Drug Expenditure of the pharmacy of RHTC for the financial year 2016-17 was calculated by adding the individual drug cost for the year which amounted to Rs.8, 69,253. On following ABC analysis A,B and C categories had the following items as 22.82%(n=21drugs) ,20.65%(n=19 drugs) and 56.53%(n=52drugs) respectively in terms of quantity and amounting for about 69.05% (Rs.6,00,256), 20.22% (Rs.1,75,834) and 0.71% (Rs.93,161) respectively in terms of cost. On following VED analysis V, E and D categories had the following items as 28.26%(n=26 drugs),46.73%(n=43drugs) and 25.01%(n=23 drugs) respectively in terms of quantity and amounting for about 4.51% (Rs.39,284), 57.14% (Rs.4,96,715) and 38.33% (Rs.3,33,252) respectively in terms of cost. On following ABC-VED matrix model method of analysis Categories I, II, III were 49.96%, 42.38%, 7.66% respectively in terms of quantity and amounting for about 72.12%(Rs.6,26,926), 25.71% (Rs.2,23,443) and 2.17% (Rs.18,882) respectively in terms of cost. The ABC - VED matrix method combines the results of both ABC and the VED analysis culminating in the better management of the expenditure based on the priority needs of the drug. Thus this ABC-VED analysis plays a vital role in identifying the required quantity and category of drugs that has to be purchased and optimally utilized in the health centre. Here the category I drugs contributed to the maximum amount in terms of quantity and cost. This also helps in vigilant allocation of funds for procuring drugs and helps in eliminating unnecessary stocking and out of stock crisis situations. If this inventory technique is routinely followed in any health facility, the economic outcomes will be better.